2020
DOI: 10.3892/etm.2020.9026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vortioxetine on depression model rats and expression of BDNF and Trk B in hippocampus

Abstract: Effects of Vortioxetine on the expression of brain-derived neurotrophic factor (BDNF) and tyrosine kinase B (Trk B) in hippocampus of depressive rats were investigated. Forty-five SD rats were randomly divided into three groups: model control, Vortioxetine and normal control group, with 15 rats in each group. The changes of body mass were recorded within 5 weeks, and the open field test, sugar water preference test and Morris water maze test were performed to evaluate the behavior and mental status of the rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Depression is considered a common mental illness leading to upset or anxiety, with a high incidence rate in the world. Depression may lead to suicidal thoughts and behavior, or mental illness manifestations, for example, fantasy or delusion (Sun et al, 2020). The World Health Organization statistics show that more than three hundred million people around the world (4.4%) endure from depression (World Health Organization (WHO)., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression is considered a common mental illness leading to upset or anxiety, with a high incidence rate in the world. Depression may lead to suicidal thoughts and behavior, or mental illness manifestations, for example, fantasy or delusion (Sun et al, 2020). The World Health Organization statistics show that more than three hundred million people around the world (4.4%) endure from depression (World Health Organization (WHO)., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) is the most prominent neurotrophic factor which shows decreased expression and function with depression and reveals an improvement by the antidepressant therapy (Zhou et al, 2017;Sun et al, 2020). The BDNF protein along with mRNA in the hippocampus of mice with depression was significantly reduced by learned helplessness (Su et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the recent marketing authorization, molecular studies on the pharmacological actions of vortioxetine are limited until now. For example, Yu et al , Lu et al and Sun et al ., ( Yu et al, 2017 ; Lu et al, 2018 ; Sun et al, 2020 ) all reported that vortioxetine administration significantly increased the hippocampal brain-derived neurotrophic factor (BDNF) -cAMP-response element binding protein (CREB) signaling cascade in rodent models of depression. Du Jardin et al ., ( du Jardin et al, 2016 ) showed that a single dose of vortoxetine increased the expression of several plasticity-related genes (mTOR, Mglur1, Pkcα, Homer3, Spinophilin, and Synapsin3) in the rat frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“… 88 Moreover, VO increases the level of the BDNF, restoring lost neurons, and potentially contributes to recovery from chronic pain. 62 , 89 92 …”
Section: Mechanism Of Actionmentioning
confidence: 99%